2014
DOI: 10.1074/mcp.m114.039073
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Phosphoproteome and Kinase-substrate Networks in the Mouse Testis

Abstract: Spermatogenesis is a complex process closely associated with the phosphorylation-orchestrated cell cycle. Elucidating the phosphorylation-based regulations should advance our understanding of the underlying molecular mechanisms. Here we present an integrative study of phosphorylation events in the testis. Large-scale phosphoproteome profiling in the adult mouse testis identified 17,829 phosphorylation sites in 3955 phosphoproteins. Although only approximately half of the phosphorylation sites enriched by IMAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…Many studies have also reported that VPA can cause decreases in sex hormones, including testosterone (Hamza & Amin, ; Ocek et al, ; Sukhorum & Iamsaard, ; Wasilewska‐Dziubinska et al, ; Zhao et al, ), which is crucial to the development process and regulation of micronutrient secreting activity of the seminal vesicle, especially in mammals (Higgins & Burchell, ; Tao, Lei, & Rao, ). This hormonal decrease has been explained by the fact that VPA treatment leads to low expressions of androgen receptor (AR) and cholesterol side‐chain cleavage enzyme (P450scc) in rats (Qi et al, ; Sukhorum & Iamsaard, ). Consequently, adverse effects may result, such as seminal atrophy, histopathological alterations and secretion reduction (including biochemical parameters), as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have also reported that VPA can cause decreases in sex hormones, including testosterone (Hamza & Amin, ; Ocek et al, ; Sukhorum & Iamsaard, ; Wasilewska‐Dziubinska et al, ; Zhao et al, ), which is crucial to the development process and regulation of micronutrient secreting activity of the seminal vesicle, especially in mammals (Higgins & Burchell, ; Tao, Lei, & Rao, ). This hormonal decrease has been explained by the fact that VPA treatment leads to low expressions of androgen receptor (AR) and cholesterol side‐chain cleavage enzyme (P450scc) in rats (Qi et al, ; Sukhorum & Iamsaard, ). Consequently, adverse effects may result, such as seminal atrophy, histopathological alterations and secretion reduction (including biochemical parameters), as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such proteins are modified by phosphorylation on tyrosine residue of translated proteins. TyrPho proteins are involved in cellular proliferation, division, growth and differentiation (Koromilas, ; Qi et al, ; Wang, Peterson, & Loring, ). Originally, TyrPho proteins were demonstrated to have essential roles in sperm capacitation and the acrosome reaction process, both in vivo and in vitro (Buffone, Kim, Doak, Rodriguez‐Miranda, & Gerton, ; Kwon, Rahman, & Pang, ; Naz & Rajesh, ; Romarowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro methods are not effective in reflecting in vivo activities of kinases, which is why MS-based methods are needed for evaluating kinase activity [82,83]. An approach to link phosphoproteomics data with the activity of kinases was presented by Qi et al [84], which is known as kinase activity analysis (KAA). CLUE (CLUster Evaluation) is a method designed specifically for phosphoproteomics data [85], based on the hypothesis that phosphosites targeted by the same kinase will show similar temporal profiles.…”
Section: Tools For Detection Of Phosphosites and Kinase Activity Frommentioning
confidence: 99%
“…Another approach to link phosphoproteomics data with the activity of kinases was presented in a publication from Qi et al [Qi et al, 2014], which they termed kinase activity analysis (KAA). In this study, the authors collected phosphoproteomics data from adult mouse testis in order to investigate the process of mammalian spermatogenesis.…”
Section: Kaa (Kinase Activity Analysis)mentioning
confidence: 99%
“…As a means to extract functional insight, methods to infer kinase activities from phosphoproteomics data based on prior-knowledge about kinase-substrate relationships have been put forward [Qi et al, 2014;Casado et al, 2013;Yang et al, 2015;Mischnik et al, 2015]. The knowledge about kinase-substrate relationships, compiled in databases like PhosphoSitePlus [Hornbeck et al, 2015] or Phospho.ELM [Dinkel et al, 2011], covers only a limited set of interactions.…”
Section: Introductionmentioning
confidence: 99%